Pengujian Tahanan Isolasi Pada Transformator Distribusi 160 kVA Di PT. PLN (PERSERO) UP3 Bengkulu - Indra, Mandalahi Haldigian; Yanolanda Suzantry Handayani; Priyadi, Irnanda (UNIB Press, 2022)
The power transformer is a high voltage equipment that functions as a distributor of electric power from high voltage to low voltage or from low voltage to high voltage. If the transformer's isolation condition deteriorates, it can have an impact on operating failure and the most fatal is that the transformer is damaged which can cause electrical system disturbances. To overcome this it is necessary to test the insulation resistance. This test is carried out using the polarization index method to determine the feasibility of the insulation resistance in the transformer. The use of this method is the most accurate and effective way to determine the feasibility of insulation resistance in transformers at distribution substations in Indonesia. This study took data at the location of PT. PLN (Persero) UP3 Bengkulu. In the insulation resistance test, the polarity index measurement results are obtained. Based on the data that has been collected then proceed with calculations and analysis to obtain better results. The ground-primary polarization index value shows that it is in good condition with a primary-ground value of 1.25 and a secondary-ground polarization index value of 1.5 (good standard between 1.25 – 2.0).